The State of Standards do they help us do our job, or do they just get in the way?. - Manes, Anne Thomas (SOA webservices journal.)
There is an old saying among standards wonks : "The most wonderful thing about standards is that there are so many of them." And this truism is more applicable today than ever before. There are so many WS-* specifications, I've started referring to them as WS-Vertigo.